Mapping elemental distributions in submarine hydrothermal sulfide smokers using proton induced X-ray emission - Yeats, C; Belton, D; Laird, J S; Ryan, C G (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2010)
PIXE analysis using a 3 MeV proton beam on the CSIRO Nuclear Microprobe was carried out on samples of four typical undersea sulfide chimneys from the Rogers Ruins and Fenway hydrothermal sites, PACMANUS field, Eastern Manus Basin, Papua New Guinea. The ability of PIXE to map the spatial association of trace elements within the sulfides across multiple mineralogical zones provides important insights into the mode of formation of structures and the nature of interaction between ∼250 and 350 °C hydrothermal fluids and 3–4 °C ambient seawater within the chimney walls.
Keywords: AUV ABE (Autonomous Benthic Explorer); ROV Jason (Remotely Operated Vehicle)